Activating the local community (theoretical grounds and examples of good practices of the revival of the idea of active neighbourhood) - Słupska , Kamila (Kultura-Społeczeństwo-Edukacja, 2020)
This paper focuses on the issue of activating the local community, including its conditions and manifestations, and putting strong emphasis on the category of community potential, which is a multifaceted and dynamic phenomenon, contributing to changes in various areas of social life. Particular attention was paid to neighbourhood activity and its stimulation, including related initiatives, the importance of which was highlighted, while selected examples of good practices, implemented both within projects, organised campaigns, as well as spontaneous individual actions were brought up.